Voltammetric determination of hydrochlorothiazide at a modified carbon paste electrode with polypyrrole nanotubes - Arefeh Mohammadnavaz; Fariba Garkani (International Association of Physical Chemists (IAPC), 2023)
In this paper, the electrochemical behavior of hydrochlorothiazide (HCTZ) is described using carbon paste electrodes modified with polypyrrole nanotubes (PPy-NTs/CPEs) at pH value 7. Experiments revealed that the presence of HCTZ greatly impacts the electrochemical behavior of modified CPEs. The synthesized PPy-NTs were utilized as a sensing material for the electrochemical detection of HCTZ and were investigated by cyclic voltammetry (CV), differential pulse voltammetry (DPV) and chronoamperometry. The key experiment conditions, including supporting electrolyte and electrolyte pH, were studied and optimized. Under optimized conditions, the prepared sensor displayed the linear relationships for the concentrations of HCTZ from 5.0 to 400.0 μM (R2 = 0.9984). The detection limit of the PPy-NTs/CPEs sensor was found to be 1.5 μM using the DPV method. The PPy-NTs is highly selective, stable and sensitive for the determination of HCT. Therefore, we believe the newly prepared PPy-NTs material can be useful for different electrochemical applications.